Clinical research Intraocular matrix metalloproteinase 2 and 9 in patients with diabetes mellitus with and without diabetic retinopathy - Kłysik, Anna B.; Naduk-Kik, Julia; Hrabec, Zbigniew; Goś, Roman; Hrabec, Elżbieta (Archives of Medical Science, 2010)
Introduction: We aimed to investigate activities of metalloproteinases 2 (MMP-2) and MMP-9 in aqueous humour of patients with diabetes mellitus with various stages of diabetic retinopathy. Material and methods: We included 36 samples of aqueous humour of patients suffering from diabetes mellitus, undergoing routine cataract surgery. Seven of them suffered from proliferative diabetic retinopathy (PDR), 3 had diabetic maculopathy and the remaining 26 had background or minimal background retinopathy only. Metalloproteinases 2 and MMP-9 activities in aqueous humour were measured by gelatin zymography combined with the densitometric imaging system. Total protein content in aqueous humour samples was also assessed. Results: Metalloproteinases 2 activities were present in almost all samples of aqueous humour (32 of 36) and were 2.6-fold higher in patients who suffered from diabetic ocular complications (p < 0.0001). Activities of MMP-2 correlated well with the duration of the disease (correlation = 0.37, p = 0.03) and tended to correlate with total protein levels in aqueous humour (correlation = 0.43, p = 0.06). Metalloproteinases 9 activities were observed only in 2 of 7 patients with proliferative diabetic disease and the enzyme was absent from aqueous humour samples of patients without proliferative retinopathy. Conclusions: Increased activities of MMP-2 in aqueous humour of patients with PDR may be related to the disease process and support the hypothesis that MMP-2 may be of particular importance in diabetic retinal neovascularization. MMP-9 may be activated at a certain disease stage only.